Study guides

Q: What is -y minus 12?

Write your answer...

Submit

Related questions

It is y - 12.

it depends,if y = 0 the answer is -12 if y = 5 then the answer is 368

Y - 12 < -10 Add 12 to both sides: Y < 2

12

If you mean 3y+24 = y-12 then the value of y works out as -18

-9

It is: y^2 -13y +12 = (y-1)(y-12) when factored

it 's the variable like if i give you the equation 1+y= 13. you would minus 1 on the right side from the 1 and then minus 1 from the 13 then you get this y=12.

y² - y - 6 = (y + 2)(y - 3)

What is 3x-6y=12

17

y2-y-72 is an algebraic expression that can be factored as: (y+8)(y-9)

-8-5y = 12-9y 9y-5y - 12+8 4y = 20 y = 5

y2-4y-32 = (y+4)(y-8) when factored

No.

2.5

y squared-y-72 is an algebraic expression because it does not contain an equality sign.

-12 minus 4 is -16.

Let y= ab+(- a)(b) +(-a)(-b) factor out -a y= ab+(-a){b+(-b)} y=ab+(-a)(0) y =ab -------------------(1) now factor out b y= b{a+(-a)}+(-a)(-b) y= b(0) +(-a)(-b) y= (-a)(-b)-----------------(2) equate (1) and (2) (-a)(-b)=ab minus x minus = positive

y squared minus 9 (y*y)- 9 cannot be solved because there is no given value for 9.

negative two thirds

22

y + 9

A negative minus a negative turns the latter into a plus positive,for example -6 minus -3 would be :-6 ++ 3 = -3A minus negative always turns into a plus positive...To get more Specific:Suppose x and y are two POSITIVE numbers so that -x and -y are negative. Then a negative minus a negative = (-x) - (-y) = -x +yIf x > y the answer is negativeIf x = y the answer is zeroIf x < y the answer is positive

The answer depends on the value of y. For example, when y = 0, 8y2 + 6y - 2 = -2 when y = 1, it is 12